2016
DOI: 10.21037/tau.2016.06.06
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculatory dysfunction in the treatment of lower urinary tract symptoms

Abstract: The link between lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH) and sexual dysfunction is well established. Sexual dysfunction can encompass both ejaculatory dysfunction (EjD) and erectile dysfunction (ED). Ejaculatory dysfunction can consist of premature ejaculation, delayed ejaculation, retrograde ejaculation, anejaculation, decreased force of ejaculation and pain upon ejaculation. The impact of different medical and surgical therapies on ejaculatory function will be revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 60 publications
1
26
0
3
Order By: Relevance
“…Utilizing light wavelengths of 532 nm, which is preferentially absorbed by hemoglobin, the GreenLight laser has emerged as an alternative therapy to TURP for the treatment of BPH via rapid vaporization of the transitional zone of the prostate [26, 43•]. Results from the GOLIATH prospective trial comparing GreenLight photoselective vaporization of the prostate (PVP) to TURP showed no significant difference between rates of REj and IIEF-5 scores between the two procedures at the 1-and 2-year follow-ups, respectively [44, 45].…”
Section: Bph Surgeries and Sexual Dysfunctionmentioning
confidence: 99%
“…Utilizing light wavelengths of 532 nm, which is preferentially absorbed by hemoglobin, the GreenLight laser has emerged as an alternative therapy to TURP for the treatment of BPH via rapid vaporization of the transitional zone of the prostate [26, 43•]. Results from the GOLIATH prospective trial comparing GreenLight photoselective vaporization of the prostate (PVP) to TURP showed no significant difference between rates of REj and IIEF-5 scores between the two procedures at the 1-and 2-year follow-ups, respectively [44, 45].…”
Section: Bph Surgeries and Sexual Dysfunctionmentioning
confidence: 99%
“…Ejakülatın retrograd olarak mesaneye akışına, patolojik olarak açık olan internal vezikal sfinkter ya da mesane boynu izin verir. [4] Fakat, klinik, fizyolojik ve anatomik bulguların bazıları bunun böyle olmayabileceğini göstermiştir. Videoürodinamik çalışmalar ise, persistan olarak açık mesane boynu olan hastaların antegrad ejakülasyona sahip olabildiğini ortaya koymuştur.…”
Section: Discussionunclassified
“…[2] Retrograd ejakülasyon seksüel fonksiyon üzerindeki etkisi yanında genel yaşam kalitesi ile de ilişkilidir. TUR-P sonrası retrograd ejakülasyon sıklığı seriler arasında çeşitlilik göstermekle beraber %47,8 [3] ve %65 [4] gibi farklı oranlar verilmiştir.…”
Section: Gereç Ve Yöntemunclassified
See 1 more Smart Citation
“…A link between sexual dysfunction and lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) has been reported [ 1 ]. Sexual dysfunction includes erectile dysfunction (ED) and ejaculatory dysfunction, and ejaculatory dysfunction includes premature ejaculation, retrograde ejaculation, delayed ejaculation, painful ejaculation, and decreased force of ejaculation [ 1 ]. Transurethral resection of the prostate (TURP) remains the standard treatment for symptomatic BPH, which occurs in about 10% to 20% of men over 40 years of age [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%